2015
DOI: 10.2147/ndt.s77391
|View full text |Cite
|
Sign up to set email alerts
|

Medium-to-high prevalence of screening-detected parkinsonism in the urban area of Tehran, Iran: data from a community-based door-to-door study

Abstract: IntroductionParkinsonism occurs in all ethnic groups worldwide; however, there are wide variations in the prevalence rates reported from different countries, even for neighboring regions. The huge socioeconomic burden of parkinsonism necessitates the need for prevalence studies in each country. So far, there is neither data registry nor prevalence information on parkinsonism in the Iranian population. The aim of our study was to estimate the prevalence rate of probable parkinsonism in a huge urban area in Iran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
0
9
0
2
Order By: Relevance
“…This Population-based door-to-door survey was performed in the metropolitan area of Tehran, Iran consisting of 22 urban districts during October 2011 and January 2012. Present study is a part of a larger project designed to study the epidemiologic features of the major neurological disorders, which has been previously described [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…This Population-based door-to-door survey was performed in the metropolitan area of Tehran, Iran consisting of 22 urban districts during October 2011 and January 2012. Present study is a part of a larger project designed to study the epidemiologic features of the major neurological disorders, which has been previously described [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…In US it is about 150 per 100,000 in all ages and reaches to approximately 800 per 100,000 at 70 to 85 (7). Epidemiological studies in Iran showed that its prevalence is medium -to-high and estimated to be more than 200 per 100,000 people (8). It is actually more frequent in men than women and progresses faster in male than female patients (5).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of PD was estimated at 222.9 per 100,000 people, with a male-to-female ratio of 1:62 in Tehran, Iran (2). Besides motor symptoms, such as bradykinesia, rigidity, and tremor, nonmotor symptoms, including fatigue, mood disorders, pain, and cognitive impairment, are major factors leading to disability (3).…”
Section: Introductionmentioning
confidence: 99%